(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The paper the organizational activities of informational security in the secondary school are considered In particular the planning of organizational activities on stages of the lifecycle of the system of information security of educational computer complex is proposed. There are purified the methods of unification for the software installed at the pupils’ workstations. There is developed the tentative calendar plan of regular activities and main approaches to the management of system of informational security of educational computer complex on the basis of hardware-software level and the organization of antivirus security in computer lab is described